Mortality Related to Chagas Disease and HIV/AIDS Coinfection in Brazil - Francisco Rogerlândio Martins-Melo; Alberto Novaes Ramos; Carlos Henrique Alencar; Jorg Heukelbach (Journal of Tropical Medicine)
Chagas disease in patients with HIV infection represents a potentially serious event with high case fatality rates. This study describes epidemiological and clinical aspects of deaths related to Chagas disease and HIV/AIDS coinfection in Brazil, 1999–2007. We performed a descriptive study based on mortality data from the nationwide Mortality Information System. Of a total of about 9 million deaths, Chagas disease and HIV/AIDS were mentioned in the same death certificate in 74 cases. AIDS was an underlying cause in 77.0% (57) and Chagas disease in 17.6% (13). Males (51.4%), white skin color (50%), age group 40–49 years (29.7%), and residents in the Southeast region (75.7%) were most common. Mean age at death was significantly lower in the coinfected (47.1 years [SD ± 14.6]), as compared to Chagas disease deaths (64.1 years [SD ± 14.7], P<0.001). Considering the lack of data on morbidity related to Chagas disease and AIDS coinfection, the use of mortality data may be an appropriate sentinel approach to monitor the occurrence of this association. Due to the epidemiological transition in Brazil, chronic Chagas disease and HIV/AIDS coinfection will be further complicated and require the development of evidence-based preventive control measures.